Perhitungan Harga Pokok Produksi dan Harga Pokok Penjualan Terhadap Laba Bersih (Studi Kasus Pabrik Tempe Istiqomah Bandar Lampung) - Angelica, Putri; Hadi, Aminah (Jurnal EMT KITA, 2024)
The aim of this research is to identify the appropriate method for calculating the Cost of Goods Production at the Istiqomah Tempe Factory and to identify how to determine the Cost of Goods Sold at the Istiqomah Tempe Factory. The research category that will be used is descriptive analysis. The research methodology that will be used in the research is descriptive analysis. Descriptive Analysis is a method that describes a problem by explaining existing data and research objects, written into a paragraph and obtaining a conclusion to solve the existing problem. The results obtained at full cost create higher expenses. Calculations using Variable Costing could be a good option to apply, because the Variable Costing method only calculates the budget involved in the manufacturing process into the COGS. It can be determined from the results of the analysis carried out if the COGS calculation to decide the selling price determined by the cost variable more closely reflects the budget spent by the business owner.